Determination of an efficient regeration protocol for Bangladeshi peanut varieties (Arachis hypogaea L.) - Chowdhury, Shahana (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2014.